The Principle of Equity in the Implementation of the National Health Insurance Program at Mission Lebak Hospital Through Quality Control and Cost Control - Denny Hardianto; Endang Wahyati Yustina; Daniel Budi Wibowo (SOEPRA, 2022)
Abstract: The National Health Insurance Program is a provision of Law No. 40 of 2004 About the National Social Security System; in its implementation, various principles have been developed as the philosophical foundations that implementing parties must adhere to. In addition to the social insurance principle, the equity principle is used as a guiding principle while providing services to National Health Insurance participants. In practice, however, this equity idea has not been fully and uniformly grasped by all parties. In the meantime, the National Health Insurance members must utilize quality control and cost-control instruments in the delivery of health services. In truth, the Health Social Security Agency of Indonesia and the Misi Lebak Hospital are unable to maintain low costs.This study aims to establish the equity principle in the implementation of the National Health Insurance program, as well as the procedures for quality control and cost-control instruments in the National Health Insurance program, and how hospitals are administered. The Misi Lebak Hospital's objective is to implement equality principles in the National Health Insurance program by controlling quality and costs. This research method employs a sociologically-based legal strategy with descriptive parameters. In this study, the combination approach was used for data analysis. The research was done in Lebak Regency, which is where Misi Lebak Hospital is located. It is a Class C hospital that is also an Advanced Level Referral Health Facility. According to the research conducted, the Misi Lebak Hospital achieved the equity principle in implementing the National Health Insurance program through quality control and cost-control management. Medical services or medical benefits offered to National Health Insurance participants do not vary based on their membership rights, which only change the supply of non-medical advantages. The results demonstrated that the meaning of the equity principle shifted from general to specific. Thus, the systems for quality control and cost-control instruments at the Misi Lebak Hospital utilize the same principle. The contract between the Health Social Security Agency of Indonesia and the Advanced Level Referral Health Facility specifies that hospitals must adhere to the quality and cost indicators outlined in the agreement. Each organizer should apply synergy in carrying out their tasks and responsibilities and provide the appropriate supervision to achieve the National Health Insurance program's objectives.Keyword: equity principle, quality control, cost controlAbstrak: Program JKN merupakan amanah dari UU No 40 Tahun 2004 tentang Sistem Jaminan Sosial Nasional (SJSN), dalam pelaksanaannya telah ditetapkan beberapa asas dan prinsip yang menjadi landasan filosofi yang harus dipatuhi oleh pihak-pihak pelaksana. Prinsip ekuitas menjadi salah satu prinsip penting disamping prinsip asuransi sosial yang dijadikan pedoman dalam pelayanan pada peserta JKN. Namun dalam pelaksanaannya, prinsip ekuitas ini belum sepenuhnya dipahami secara seragam oleh semua pihak. Sementara itu dalam penyelenggaraan layanan kesehatan pada peserta JKN perlu menggunakan instrumen kendali mutu dan kendali biaya. Dalam kenyataannya kendali biaya di pihak BPJSK dan RS Misi Lebak kurang berjalan baik.Tujuan dari penelitian ini adalah: mengidentifikasi prinsip ekuitas dalam pelaksanaan program JKN, mengetahui pengaturan tentang kendali mutu dan kendali biaya dalam program JKN, dan mengidentifikasi cara RS. Misi Lebak dalam melaksanakan prinsip ekuitas dalam program JKN melalui kendali mutu dan kendali biaya. Metode penelitian ini menggunakan pendekatan yuridis sosiologis dengan spesifikasi deskriptif. Mix methode diaplikasikan dalam penelitian ini untuk analisis datanya. Lokasi dan subyek penelitian berada di RS Misi Lebak, suatu rumah sakit Kelas C sebagai FKRTL yang memberikan layanan program JKN di Kabupaten Lebak.Dari penelitian yang dilakukan, didapatkan hasil bahwa RS Misi Lebak telah memenuhi prinsip ekuitas dalam pelaksanaan program JKN melalui kendali mutu dan kendali biaya. Pelayanan medis atau manfaat medis yang diberikan kepada peserta JKN tidak dibeda-bedakan berdasarkan hak kepesertaannya, yang berbeda hanya pada pemberian manfaat non medis. Hasil penelitian menunjukkan bahwa prinsip ekuitas mengalami pergeseran makna yaitu secara umum dan secara khusus. Sehingga pengaturan kendali mutu dan kendali biaya di RS Misi Lebak juga berlaku hal yang sama. Pengaturan secara khusus mewajibkan rumah sakit untuk mematuhi indikator mutu dan biaya yang telah ditetapkan dalam kontrak antara BPJSK dengan FKRTL. Setiap pihak penyelenggara hendaknya bersinergi dalam melakukan tanggungjawab dan kewajiban serta melaksanakan pengawasan yang diperlukan agar tujuan program JKN ini dapat tercapai.Kata kunci: prinsip ekuitas, kendali mutu, kendali biaya